Nelsinho, o vampiro de almas femininas - Munhoz, Virgínia Magda Alexandre (2008)
This study aims to examine the protagonist of the book The vampire of Curitiba, of the writer Dalton Trevisan, the character Nelsinho, which can be found in the fifteen stories of the book. The analysis will be made under the perspective of the studies of gender, Stylistic and social history, and is divided into three chapters: Being the first chapter entitled "Women, men and vampires," the second "A vampire in Curitiba" and the third "The seduction in movement".